The Need to Endorse Corporate Environmental Responsibility and the Government Role in Ethiopia - Abate, Ayalew Bishaw (Bahir Dar University Journal of Law, 2023)
In promoting corporate environmental responsibility (CER) governments play key roles. CER develops a common corporate environmental policy framework and commits itself to action areas such as awareness creation, partnering, soft law development and mandating. As such it encourages the business sector to play its role in protecting the environment. In this article an attempt has been made to examine whether the Ethiopian government has played these key roles as mentioned. Accordingly, CER has been described, the government action areas have been identified and elaborated, and whether there is a need to endorse CER in Ethiopian and whether the government plays a role in these areas have been assessed. Pertinent laws and policy documents including the related literature have been consulted and reviewed. The findings show that, although there are convincing reasons for the Ethiopian government to play its own roles, there are only limited efforts. Moreover, some self-initiated business community efforts donâ€™t also have government support and monitoring. Therefore, the government needs to develop a common corporate environmental policy framework and commits itself properly to the CER action areas so as to endorse and/or promote CER. Important suggestions are forwarded that can help make decisions in this regard.